Squeezed K+K- correlations in high energy heavy ion collisions - Dudek, Danuce M. [UNESP]; Padula, Sandra S. [UNESP] (Amer Physical Soc, 2010)
The hot and dense medium formed in high energy heavy ion collisions may modify some hadronic properties. In particular, if hadron masses are shifted in-medium, it was demonstrated that this could lead to back-to-back squeezed correlations (BBC) of particle-antiparticle pairs. Although well-established theoretically, the squeezed correlations have not yet been discovered experimentally. A method has been suggested for the empirical search of this effect, which was previously illustrated for phi phi pairs. We apply here the formalism and the suggested method to the case of K+K- pairs, since they may be easier to identify experimentally. The time distribution of the emission process plays a crucial role in the survival of the BBC's. We analyze the cases where the emission is supposed to occur suddenly or via a Lorentzian distribution, and compare with the case of a Levy distribution in time. Effects of squeezing on the correlation function of identical particles are also analyzed.